Two-component super-strong epoxy glass flake paint and preparation method thereof

The two-component ultra-strong epoxy glass flake paint formula solves the problem of the difficulty in balancing wear resistance and corrosion resistance in epoxy glass flake coatings, forming a dense and wear-resistant coating suitable for marine facilities in marine environments.

CN121022218APending Publication Date: 2025-11-28SHENZHEN QIONGBA WATERPROOF TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511381977.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing epoxy glass flake coatings struggle to balance abrasion resistance and corrosion resistance, and are particularly susceptible to damage in high-scouring marine environments, failing to meet the stringent requirements of offshore facilities.

Method used

The two-component ultra-strong epoxy glass flake paint formula contains a specific ratio of bisphenol A and bisphenol F epoxy resins, trimethylolethane triglycidyl ether resin, petroleum resin and other components. Combined with high Mohs hardness reinforcing materials and dense structure design, it forms a flexible and hard coating. The reinforcing materials and methods form a flexible coating, which improves wear resistance and corrosion resistance.

Benefits of technology

It achieves high wear resistance, corrosion resistance, cathodic disbondment resistance, salt spray resistance and high adhesion, is suitable for marine environments, meets multiple anti-corrosion standards, and is suitable for underwater and splash zones of offshore facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005614327930000061
    Figure BDA0005614327930000061
  • Figure BDA0005614327930000071
    Figure BDA0005614327930000071
  • Figure BDA0005614327930000091
    Figure BDA0005614327930000091
Patent Text Reader

Abstract

The invention relates to the technical field of coating preparation, and particularly discloses a two-component super-strong epoxy glass flake paint and a preparation method thereof. The two-component super-strong epoxy glass flake paint is characterized by comprising a main paint and a curing agent, the main paint comprises the following components in parts by weight: 5-15 parts of bisphenol A epoxy resin; 15 to 25 parts of bisphenol F epoxy resin; 5-10 parts of petroleum resin; 3 to 5 parts of trimethylolethane triglycidyl ether resin; 0.1 to 0.5 part of a dispersant; 0.1 to 0.5 part of a defoaming agent; 10 to 15 parts of titanium dioxide; 10 to 25 parts of glass flakes; 15-25 parts of a reinforcing material; 5-25 parts of a filler; 10-20 parts of an anti-rust pigment; 1-5 parts of a silane coupling agent; 1-5 parts of an anti-sagging auxiliary agent; the curing agent comprises the following components in parts by weight: 20-25 parts of a polyamide curing agent; 30 to 40 parts of an epoxy-amine adduct; 25 to 35 parts of modified alicyclic amine; and 10-15 parts of modified fatty amine. The two-component super-strong epoxy glass flake paint has high wear resistance and corrosion resistance at the same time; the problem that high wear resistance and high corrosion resistance of an existing coating are difficult to consider at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of paint preparation, in particular to a two-component super-strong epoxy glass flake paint and a preparation method thereof. BACKGROUND

[0002] Ships, offshore platforms, offshore steel structures are in the marine environment for a long time, and the corrosion of seawater on metal is more serious and rapid than on land. If protective measures are not taken, the corrosion rate is very fast. Therefore, corrosion-resistant paint is needed to protect ships, naval vessels, offshore oil drilling platforms, wharf steel piles and offshore steel structures from seawater corrosion. Environmental protection and energy saving have always been the national policy of our country, and with the release of GB / T30981 Industrial Protective Coatings Harmful Substance Limit Standard at the end of 2020, water-based, powder, high solid, solvent-free, etc. are the future development direction of coatings.

[0003] Offshore facilities exist in three areas in the ocean: splash zone, underwater zone, and atmospheric zone. The corrosion rate of the splash zone and underwater zone on offshore facilities is much higher than that of other areas, so the current anti-corrosion industry for offshore buildings and ships is more recognized by Norsok Standard M-501 Surface Treatment and Protective Coating, NACE SP0108 Protective Coating Control of Offshore Platform Corrosion, ISO12944-9 Color Paint and Varnish - Protective Coating System for Corrosion Protection of Steel Structures, and ISO20340 Color Paint and Varnish - Performance Requirements for Offshore Platform and Related Structure Corrosion Protection Coating System, of which M-501 is the most recognized.

[0004] In the fields of marine engineering, ships, petrochemical industry and other corrosion-prone areas, epoxy glass flake paint is a commonly used high-performance heavy-duty coating. The key functional component of the formula, glass flake, is stacked layer by layer in the coating, forming a physical barrier similar to the "labyrinth effect", which can effectively block the penetration of water, oxygen, salt spray, chemical media and other corrosion factors to the surface of the substrate (such as steel), greatly delaying the corrosion of the substrate. In harsh working conditions with strong corrosion and high wear, with the passage of time, the surface of ordinary epoxy glass flake paint coating will quickly break down, the substrate will corrode rapidly, and the corrosion medium will take advantage of the situation to enter, causing a vicious cycle of corrosion and wear. Misuse of ordinary epoxy glass flake paint in high wear environments is essentially "using a low-wear coating to withstand a wear load that exceeds its capabilities".

[0005] At present, most of the epoxy glass flake coatings on the market have the problem of high wear resistance and high corrosion resistance in the field of wear resistance and corrosion resistance. The essence of the problem is that the formula design of "corrosion priority" does not match the complex working conditions of "erosion and wear". To solve this problem, we need to break the "single performance optimization" thinking, and through the ways of composite filler synergy, resin toughness-hardness balance, gradient structure design, etc., to realize the comprehensive performance of "no compromise in corrosion resistance and no line loss in wear resistance", so as to adapt to the harsh requirements of marine environment. For example, the Chinese patent with application number 202211385835.4 and publication date of 20221107 discloses a kind of super wear-resistant epoxy glass flake coating, the coating comprises the following components: bisphenol A epoxy resin, dimer acid modified epoxy resin, trimethylol ethane triglycidyl ether, epoxy modified liquid rubber resin, dispersing agent, defoaming agent, titanium white, glass flake, reinforcing material, filler, silane coupling agent, anti-sagging aid, C9 modified tree, curing agent. In addition, the invention also discloses a preparation method and use method of the coating, which is used for treating the surface of the glass flake with silicon dioxide: the surface of the glass flake is treated with silicon dioxide, the silicon dioxide is diluted with an alcohol solvent, the glass flake is immersed and stirred in the silicon dioxide diluent, so that the glass flake can be coated with silicon dioxide, and the coated glass flake can increase the adhesion between the coating layers and improve the water vapor shielding effect. However, this technology meets the corrosion resistance, but the wear resistance is insufficient (50mg / 1000g / 1000r), and it is difficult to cope with the wear and tear of the paint film in the high scouring environment of the ocean; further improvement is needed. SUMMARY

[0006] In order to overcome at least one of the technical problems in the prior art, the present application provides a two-component super epoxy glass flake paint and a preparation method thereof.

[0007] The technical solution of the present application is as follows:

[0008] The present application first provides a two-component super epoxy glass flake paint, which comprises a main paint and a curing agent;

[0009] The main paint comprises the following components by weight:

[0010] Bisphenol A epoxy resin 5-15 parts;

[0011] Bisphenol F epoxy resin 15-25 parts;

[0012] Petroleum resin 5-10 parts;

[0013] Trimethylol ethane triglycidyl ether resin 3-5 parts;

[0014] Dispersing agent 0.1-0.5 parts;

[0015] Defoaming agent 0.1-0.5 parts;

[0016] Titanium dioxide 10-15 parts;

[0017] Glass flake 10-25 parts;

[0018] Reinforcing material 15-25 parts;

[0019] Filler 5-25 parts;

[0020] Rust preventive pigment 10-20 parts

[0021] Silane coupling agent 1-5 parts;

[0022] Anti-sagging aid 1-5 parts;

[0023] The curing agent comprises the following parts by weight of components:

[0024] Polyamide curing agent 20-25 parts;

[0025] Epoxy-amine adduct 30-40 parts;

[0026] Modified aliphatic amine 25-35 parts;

[0027] Modified aliphatic amine 10-15 parts.

[0028] Preferably, the weight ratio of the main paint and the curing agent is 4-8:1.

[0029] Most preferably, the weight ratio of the main paint and the curing agent is 5:1.

[0030] Preferably, the bisphenol A epoxy resin is selected from bisphenol A epoxy resins having a molecular weight of <400, an epoxy equivalent weight of 160-190 g / eq, and a solids content of 100%.

[0031] Preferably, the petroleum resin is selected from C10 petroleum resins.

[0032] Glass flake is a kind of flaky filler, the flat glass flake with a diameter-thickness ratio of 30-120 is arranged in parallel and overlapped in a labyrinth structure in the resin, so as to form a dense anti-permeation layer structure. The penetration of corrosive medium in the cured resin must pass through numerous tortuous paths, so the corrosion penetration distance is greatly prolonged in the corrosion-resistant coating of a certain thickness, which is equivalent to effectively increasing the thickness of the corrosion-resistant layer and improving the corrosion resistance. The impact force caused by sea waves hitting offshore facilities can cause the paint film to wear, and the white corundum, alumina and ceramic powder are the hardest abrasives, with a Mohs hardness of 10, and the addition of wear-resistant reinforcing materials can greatly improve the wear resistance of the paint film. In the prior art, it is mentioned that the performance of the corrosion-resistant medium is improved by using bisphenol A epoxy resin as the main resin, glass flake as the filler and other fillers, but the marine environment is complex, once the paint film is damaged, the metal substrate will form an electric current under the action of seawater, which will further damage the paint film. The cathodic disbonding performance is an experiment of immersing the paint film in seawater after the paint film is damaged, only the paint film can withstand the electric current and cannot be stripped to meet the requirements of offshore facilities, so a higher crosslinking density is required. The trimethylol ethane triglycidyl ether resin has a high crosslinking point and forms a dense network structure. Therefore, the trimethylol ethane triglycidyl ether resin, bisphenol A resin and bisphenol F epoxy resin are combined to form a flexible, hard and dense coating, so that the epoxy glass flake paint has high wear resistance and corrosion resistance.

[0033] Further preferably, the C9 petroleum resin is a medium-hydroxyl petroleum resin with a hydroxyl value of 80-100. Studies have shown that the C9 petroleum resin with a hydroxyl value of 80-100 can improve the adhesion to the substrate, improve the compatibility with the epoxy resin, and improve the wetting and dispersing performance of the pigment and filler.

[0034] Preferably, the trimethylol ethane triglycidyl ether resin has a molecular weight of 300-500. Studies have shown that the trimethylol ethane triglycidyl ether resin with this molecular weight can increase the crosslinking density of the coating and improve the chemical resistance.

[0035] Preferably, the glass flake is selected from 100 mesh and / or 325 mesh glass flake.

[0036] Preferably, the reinforcing material is selected from one or more mixtures of white corundum, carbon nanotubes, alumina and ceramic powder.

[0037] Preferably, the filler is selected from one or more mixtures of feldspar powder, silica powder, barium sulfate, talc powder, mica powder, aluminum powder, iron-titanium powder and phosphate.

[0038] Preferably, the anti-rust pigment is selected from one or more mixtures of zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, calcium ion exchanger.

[0039] Preferably, the epoxy-amine adduct is prepared by the following method:

[0040] The bisphenol A epoxy resin is dissolved with a solvent and heated to 80-100℃, then a mixture of aliphatic amine and alicyclic amine is added dropwise, the dropwise adding time is controlled to 2-4 hours, the dropwise adding temperature is controlled to 80-100℃, after the dropwise adding is completed, the temperature is kept for 2-4 hours, the amine value is measured, and the amine value is adjusted to 280-320 mg KOH / g, thereby obtaining the epoxy-amine adduct.

[0041] Preferably, the solvent is xylene; the mass amount of the solvent is 15-30% of the mass of the bisphenol A epoxy resin solvent.

[0042] Most preferably, the mass amount of the solvent is 20% of the mass of the bisphenol A epoxy resin solvent.

[0043] Preferably, the mass ratio of the bisphenol A resin to the mixture of aliphatic amine and alicyclic amine is 2-4:6-8; the mass ratio of the aliphatic amine to the alicyclic amine in the mixture of aliphatic amine and alicyclic amine is 2-4:6-8.

[0044] Most preferably, the mass ratio of the bisphenol A resin to the mixture of aliphatic amine and alicyclic amine is 3:7; the mass ratio of the aliphatic amine to the alicyclic amine in the mixture of aliphatic amine and alicyclic amine is 3:7.

[0045] Preferably, the aliphatic amine is selected from one or more mixtures of triethyl tetramine, tetraethyl pentamine and hexanediamine; and the alicyclic amine is selected from IPDA and / or MXDA.

[0046] The inventors have found in further research that, in the curing agent described in the present application, the epoxy-amine adduct prepared by the above-mentioned method of the present application can balance the flexibility and hardness of the paint film, thereby improving the performance of the paint film in terms of cathodic disbonding resistance, chemical resistance, salt spray resistance and the like; and the epoxy glass flake paint has good performance in terms of cathodic disbonding resistance, chemical resistance, salt spray resistance and the like.

[0047] The present application also provides a preparation method of the above-mentioned two-component super-strong epoxy glass flake paint, which comprises the following steps:

[0048] A) Preparation of the main paint

[0049] 1) Bisphenol A epoxy resin, bisphenol F epoxy resin, petroleum resin, dispersant, trimethylol ethane triglycidyl ether resin, and defoaming agent are weighed and put into a cylinder for high-speed dispersion;

[0050] 2) Add titanium dioxide and filler into the cylinder, disperse at high speed for 10-15 minutes, then grind;

[0051] 3) Discharge after grinding to ≤40μm;

[0052] 4) Mix silane coupling agent, glass flake and reinforcing material evenly and reserve;

[0053] 5) Start medium speed stirring, add the mixture obtained in step 4) into the mixture in step 3), then add anti-sagging agent and mix evenly;

[0054] 6) Filter through 80 mesh screen and package;

[0055] B) Preparation of curing agent

[0056] Weigh polyamide curing agent, epoxy-amine adduct, modified aliphatic amine and modified alicyclic amine, mix and disperse, filter through 200 mesh screen and package.

[0057] The two-component super strong epoxy glass flake paint is used by mixing the main paint with the curing agent, adding 0-5% diluent by weight of the mixture, stirring evenly and then spraying with airless spray gun. The diluent is a mixture of one or more of butanol, xylene and cyclohexanone.

[0058] Compared with the prior art, the present application has the following beneficial effects:

[0059] 1. The present application solves the problems of poor wear resistance and adhesion of the paint used for offshore facilities, solves the problem of performance decline of the paint used for offshore facilities in the underwater area and splash area after resisting seawater, and solves the problems of high solvent, low volume solid content and high VOC of traditional epoxy glass flake paint. The volume solid content of the paint is 90%, the weight solid content is ≥93%, the one-time film thickness is 400-600μm, the wear resistance (1000g / 1000r) is ≤15, the VOC is ≤80g / l, the paint film resists 95℃ seawater, salt spray, cathodic disbonding and has high adhesion. The present application is suitable for offshore facilities, and the construction method uses airless spray equipment for spraying.

[0060] 2. The super strong wear-resistant epoxy glass flake paint of the present application contains a small amount of organic solvent in the main paint and does not contain solvent in the curing agent, which is a low VOC product and has important environmental protection significance.

[0061] 3.The super wear-resistant epoxy glass flake coating of the present application meets Norsok Standard M-501 Surface Preparation and Protective Coating, NACE SP0108 Control of Corrosion by Protective Coatings for Offshore Platforms, ISO12944-9 Paints and Varnishes - Protective Coatings Systems for the Corrosion Protection of Steel Structures, ISO 20340 Paints and Varnishes - Performance Requirements for Protective Coating Systems for Offshore Platforms and Related Structures, HG / T4336-2012 Epoxy Glass Anticorrosive Coatings.

[0062] 4.The super wear-resistant epoxy glass flake coating of the present application has the advantages of wear resistance, cathodic disbonding resistance, 95℃ seawater resistance, high adhesion, salt spray resistance, etc.Compared with traditional glass flake coatings, the present coating is more suitable for underwater and splash zone of facilities in the fields of offshore drilling platforms, marine buildings, wind power pile foundations, marine equipment, cross-sea bridges, ships, shore bridges, marine piles, offshore photovoltaic supports, etc.The product has low VOC and meets GB30981 standard. DETAILED DESCRIPTION

[0063] The present application will be further described in detail below in combination with specific examples, but the examples do not limit the present application in any form.

[0064] The raw materials used in the following examples are commercially available, wherein:

[0065] The bisphenol F epoxy resin can be selected from Phoenix 830 and Nanya 170;

[0066] The bisphenol A epoxy resin can be selected from Nanya 128 and Phoenix E51;

[0067] The trimethylol ethane triglycidyl ether resin can be selected from GE-31 of Huntsman; the petroleum resin can be selected from C9 petroleum resin of Hengfeng Petroleum Chemical Co., Ltd. of Puyang; the defoaming agent can be selected from byk-051 of BYK Company and Evonik 2620-85D;

[0068] The dispersing agent can be selected from byk-182 and byk-110 of BYK Company;

[0069] The silane coupling agent can be selected from MP-200 and A-187 of Momentive;

[0070] The titanium white can be selected from R-996 of DuPont;

[0071] The polyamide curing agent can be selected from Air Products 315;

[0072] The modified aliphatic amine can be selected from Air Products 2726;

[0073] The modified aliphatic amine can be selected from Air Products 2726;

[0074] Preparation of two-component super epoxy glass flake paint

[0075] (I) The two-component super epoxy glass flake paint formula is shown in Table 1.

[0076] Table 1. Formula of two-component super epoxy glass flake paint of Examples 1-5

[0077]

[0078]

[0079] The above epoxy-amine adduct is prepared by the following method:

[0080] The bisphenol A epoxy resin is dissolved in dimethylbenzene to a mass concentration of 80%, and then heated to 90°C. A mixture of triethylenetetramine and m-xylylenediamine with a mass ratio of 3:7 is added dropwise. The mass ratio of bisphenol A resin to the mixture of triethylenetetramine and m-xylylenediamine is 3:7. The dropwise addition is controlled within 3 hours, and the dropwise addition temperature is controlled at 90°C. After the dropwise addition is completed, the temperature is kept for 2 hours. The amine value is measured, and the amine value is controlled at 300 mgKOH / g. Pour out and reserve for use.

[0081] (II) Preparation method and use method of two-component super epoxy glass flake paint

[0082] The preparation method of the paint is as follows:

[0083] A) Preparation of main paint

[0084] 1) After accurately weighing the above-mentioned weight parts of Nanya 128, Nanya 170, C9 petroleum resin, GE-31 of Hensma, byk-110, and Evonik 2620-85D, they are put into a cylinder and subjected to high-speed dispersion;

[0085] 2) After weighing DuPont's R-996, iron-titanium powder, mica powder, barium sulfate, and talc powder, they are added to the cylinder and subjected to high-speed dispersion for 10 minutes. Then zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, and calcium ion exchanger are added, and high-speed dispersion is carried out for 10-15 minutes, followed by grinding;

[0086] 3) After grinding to a fineness of ≤40 μm, the material is discharged

[0087] 4) After diluting MP-200 of Meituo with ethanol, 100-mesh glass flake, 325-mesh glass flake, white corundum, carbon nanotube, alumina, and ceramic powder are weighed and added to a high-speed stirrer. After mixing uniformly, they are reserved for use;

[0088] 5) Start medium-speed stirring, and mix the mixed glass flake and reinforcing material with the resin, filler, titanium white, and special anti-rust pigment in the ground cylinder;

[0089] 6) Take bentonite, open the medium speed stirring to prevent the flow of the anti-sticking agent into the cylinder to mix evenly;

[0090] 7) Use 80 mesh vibrating screen for filtration and packaging;

[0091] B) curing agent preparation step

[0092] 1) Take air chemical 315, self-made epoxy-amine adduct, air chemical 2726, air chemical 401 according to the weight parts described above and add them into the cylinder for standby.

[0093] 2) After dispersing the curing agent described above at medium speed for 10 minutes, filter and package with a 200 mesh filter screen.

[0094] Method for use:

[0095] Mix the main paint with the curing agent according to the weight ratio of 5:1, add 3% diluent of the weight of the mixture, stir uniformly, and then spray with airless spray gun.

[0096] The two-component super strong epoxy glass flake paint prepared by examples 1-5 is used to make a plate with airless spray equipment, and performance test is carried out, and the results are shown in table 2:

[0097] Table 2. Performance test results of two-component super strong epoxy glass flake paint prepared by examples 1-5

[0098]

[0099]

[0100] From the test results above, it can be seen that the two-component super strong epoxy glass flake paint of the present application meets the certification standards of Norsok Standard M-501 "Surface Treatment and Protective Coating", NACE SP0108 "Control of Protective Coating on Offshore Platform Corrosion", ISO 12944-9 "Color Paint and Varnish - Corrosion Protection of Protective Coating System for Steel Structure", ISO 20340 "Color Paint and Varnish - Performance Requirements of Protective Coating System for Offshore Platform and Related Structures", and HG / T4336-2012.

[0101] The specific embodiments of the present application are described in detail above, but they are only examples, and the present application is not limited to the specific embodiments described above. Any equivalent modifications and alternatives to the present application made by those skilled in the art are also within the scope of the present application. Therefore, any equivalent modifications and changes made without departing from the spirit and scope of the present application should be covered within the scope of the present application.

Claims

1. A two-component super strong epoxy glass flake paint, characterized by, A main paint and a curing agent; The main paint comprises the following components by weight: Bisphenol A epoxy resin 5-15 parts; Bisphenol F epoxy resin 15-25 parts; Petroleum resin 5-10 parts; Trimethylol ethane triglycidyl ether resin 3-5 parts; Dispersant 0.1-0.5 parts; Defoaming agent 0.1-0.5 parts; Titanium white 10-15 parts; Glass flake 10-25 parts; Reinforcing material 15-25 parts; Filler 5-25 parts; Anti-rust pigment 10-20 parts Silane coupling agent 1-5 parts; Anti-sagging aid 1-5 parts; The curing agent comprises the following components by weight: Polyamide curing agent 20-25 parts; Epoxy-amine adduct 30-40 parts; Modified alicyclic amine 25-35 parts; Modified aliphatic amine 10-15 parts.

2. The two-component super strong epoxy glass flake paint according to claim 1, characterized in that, The weight ratio of the main paint and the curing agent is 4-8:1; Most preferably, the weight ratio of the main paint and the curing agent is 5:

1.

3. The two-part ultra strong epoxy glass flake paint according to claim 1, characterized in that, The petroleum resin is selected from C9 petroleum resin.

4. The two-part ultra-strong epoxy glass flake paint according to claim 1, characterized in that, The reinforcing material is selected from one or more mixtures of white corundum, carbon nanotubes, aluminum oxide, and ceramic powder.

5. The two-part ultra-strong epoxy glass flake paint according to claim 1, characterized in that, The filler is selected from one or more mixtures of feldspar powder, silica powder, barium sulfate, talc powder, mica powder, aluminum powder, iron-titanium powder, and phosphate.

6. The two-part ultra-strong epoxy glass flake paint according to claim 1, wherein the epoxy resin is a mixture of an epoxy resin having an epoxy equivalent weight of 175-185 g / eq and an epoxy resin having an epoxy equivalent weight of 350-400 g / eq. The anti-rust pigment is selected from one or more mixtures of zinc phosphate, aluminum tripolyphosphate, zinc phosphomolybdate, and calcium ion exchanger.

7. The two-part ultra-strong epoxy glass flake paint according to claim 1, wherein the epoxy resin is a mixture of an epoxy resin having an epoxy equivalent weight of 175-185 g / eq and an epoxy resin having an epoxy equivalent weight of 350-400 g / eq. The epoxy-amine adduct is prepared by the following method: Dissolve bisphenol A epoxy resin with solvent and heat to 80-100℃, then start dropping the mixture of aliphatic amine and alicyclic amine, the dropping time is controlled in 2-4 hours, the dropping temperature is controlled in 80-100℃, after dropping, keep warm for 2-4 hours, measure the amine value, adjust the amine value to 280-320mg KOH / g, then the epoxy-amine adduct is obtained.

8. The two-component ultra-strong epoxy glass flake paint according to claim 7, characterized in that, The solvent is xylene; the mass of the solvent is 15-30% of the mass of bisphenol A epoxy resin solvent; Most preferably, the mass of the solvent is 20% of the mass of bisphenol A epoxy resin solvent.

9. The two-part ultra-strong epoxy glass flake paint according to claim 7, characterized in that, The mass ratio of bisphenol A resin to the mixture of aliphatic amine and alicyclic amine is 2-4:6-8; the mass ratio of aliphatic amine to alicyclic amine in the mixture of aliphatic amine and alicyclic amine is 2-4:6-8; Most preferably, the mass ratio of bisphenol A resin to the mixture of aliphatic amine and alicyclic amine is 3:7; the mass ratio of aliphatic amine to alicyclic amine in the mixture of aliphatic amine and alicyclic amine is 3:7; Preferably, the aliphatic amine is selected from one or more mixtures of triethyl tetramine, tetraethyl pentamine, and hexanediamine; the alicyclic amine is selected from IPDA and / or MXDA.

10. The method of preparing the two-component super strong epoxy glass flake paint according to any one of claims 1 to 9, characterized in that, Comprises the following steps: A) Preparation of main paint 1) Weigh bisphenol A epoxy resin, bisphenol F epoxy resin, petroleum resin, dispersant, trimethylol ethane triglycidyl ether resin, and defoaming agent, and put them into a cylinder for high-speed dispersion; 2) Add titanium white and filler to the cylinder, and disperse at high speed for 10-15 minutes, then grind; 3) After grinding to a fineness of ≤40μm, discharge; 4) Mix silane coupling agent, glass flake, and reinforcing material uniformly, and reserve; 5) Start medium speed mixing and add the mixture from step 4) to the mixture from step 3) ; then add the anti-skinning agent and mix well; 6) 80 mesh filter, package; B) Preparation of the curing agent Polyamide curing agent, epoxy-amine adduct, modified aliphatic amine, modified cycloaliphatic amine are weighed and mixed and dispersed, 200 mesh filter, package.

Citation Information

Patent Citations

  • A high-solid wear-resistant epoxy glass flake coating and preparation method thereof

    CN115746659B